3D geological suitability evaluation for urban underground space development – A case study of Qianjiang Newtown in Hangzhou, Eastern China. (September 2021) - Dou, Fanfan; Li, Xiaohui; Xing, Huaixue; Yuan, Feng; Ge, Weiya
Highlights: Framework of UUS geological suitability evaluation in 3D (3D-UGSE) is proposed. Implicit method enables fast automatic generation of underground geological bodies. 3D spatial analysis methods extract more evaluation factors via data integration. 3D-UGSE framework gives more evaluation results and enhances down-depth resolution. Abstract: Geological suitability evaluation for urban underground space (UUS) is essential for effective UUS utilisation and exploitation risk reduction. However, previous research was hampered by limited availability of 3D technology. The 2D data-based evaluation process has led to information loss among underground data, whilst evaluation results without 3D attributes would also impede accurate analysis and further application. This study presents a novel UUS geological suitability evaluation (3D-UGSE) framework, which accounts for the characteristics of 3D data and other practical requirements. The framework integrates a large amount of available geoscientific data with 3D technology, and contains five steps: (1) data collection and integration; (2) 3D geological model construction using implicit 3D geological modelling method with multi-source geological data; (3) 3D evaluation index system creation, considering local geological conditions based on the available data; (4) 3D thematic map production from the 3D geological models, using 3D spatial analysis methods; (5) 3D geological suitability map production, integrating all the 3D thematic maps using comprehensive evaluation methods. To evaluate this approach, we took the Qianjiang Newtown in Hangzhou (eastern China) as an example and assessed the UUS geological suitability in three dimensions. The results show that the 3D-UGSE framework can effectively integrate 2D and 3D geological information, give more reasonable and informative evaluation results, and enhance the depth resolution of the results. This approach can provide more useful information for the planning, sustainable development, and utilisation of urban underground space.